When Governments Regulate Governments. Issue 3 (18th September 2015) - Konisky, David M.; Teodoro, Manuel P.
Abstract : This article advances a political theory of regulation that accounts for the choices of regulators and regulated entities when both are governments. Leading theories of regulation assume that governments regulate profit‐maximizing firms: Governments set rules, to which firms respond rationally in ways that constrain their behavior. But often the entities that governments regulate are other governments. We argue that government agencies and private firms often face different compliance costs, and that agencies have greater incentives than firms to appeal regulations through political channels. Simultaneously, the typical enforcement instruments that regulators use to influence firm behavior may be less effective against governments. Our empirical subjects are public and private entities' compliance with the U.S. Clean Air Act and Safe Drinking Water Act. We find that, compared with private firms, governments violate these laws significantly more frequently and are less likely to be penalized for violations.